Influence of types of eggplant plant formation on productivity in the conditions of summer-autumn turnover in film greenhouses - V. I. Terekhova; A. V. Konstantinovich (Овощи России, 2020)
Relevance. The annual increase in the area under the eggplant culture in small farms and the individual sector is explained by high nutritional, dietary, taste, and also the multi-purpose use of fruits. For optimal growth and development, eggplant needs a high amount of active temperature, which greatly limits the cultivation of crops in many regions of Russia. However, the egg-plant growing area is expanded through the use of industrial and film unheated greenhouses. The development of technology elements for growing eggplant in film greenhouses is relevant, as it contributes to an increase in the area of farms.Materials and methods. The aim of the research was to substantiate the elements of the technology for growing eggplant in film unheated soil greenhouses. The studies were carried out in 2018-2019 at the base of the Educational and Scientific Production Center “Vegetable Experimental Station named after IN AND. Edelstein» RGAU-Moscow Agricultural Academy named after K.A. Timiryazev in the summer-autumn turnover in a film unheated soil greenhouse. The objects of research were varieties and F1 eggplant hybrids: F1 Borovichok, F1 Bagira, F1 Tender, F1 Patio Trio, as a control they used a hybrid F1 Pelican; eggplant varieties: Mushroom pleasure, Black handsome, Don Quixote, they used the Frant variety as a control.Results. In general, based on the results of studying the influence of the formation of two and three stalked eggplant varieties and hybrids on the total yield in the conditions of summer-autumn turnover in film soil greenhouses, we recommend that all studied hybrids and varieties be grown in three shoots.